Matrix-Immobilized BMP-2 on Microcontact Printed Fibronectin as an in vitro Tool to Study BMP-Mediated Signaling and Cell Migration - Hauff, Kristin; Zambarda, Chiara; Dietrich, Miriam; Halbig, Maria; Grab, Anna Luise; Medda, Rebecca; Cavalcanti-Adam, Elisabetta Ada (Frontiers in Bioengineering and Biotechnology, 2015)
During development, growth factors (GFs) such as bone morphogenetic proteins (BMPs) exert important functions in several tissues by regulating signaling for cell differentiation and migration. In vivo, the extracellular matrix (ECM) not only provides support for adherent cells, but also acts as reservoir of GFs. Several constituents of the ECM provide adhesive cues, which serve as binding sites for cell trans-membrane receptors, such as integrins. In conveying adhesion-mediated signaling to the intracellular compartment, integrins do not function alone but rather crosstalk and cooperate with other receptors, such as GF receptors. Here, we present a strategy for the immobilization of BMP-2 onto cellular fibronectin (cFN), a key protein of the ECM, to investigate GF-mediated signaling and migration. Following biotinylation, BMP-2 was linked to biotinylated cFN using NeutrAvidin as cross-linker. Characterization with quartz crystal microbalance with dissipation monitoring and enzyme-linked immunosorbent assay confirmed the efficient immobilization of BMP-2 on cFN over a period of 24 h. To validate the bioactivity of matrix-immobilized BMP-2 (iBMP-2), we investigated short- and long-term responses of C2C12 myoblasts, which are an established in vitro model for BMP-2 signaling, in comparison to soluble BMP-2 (sBMP-2) or in absence of GFs. Similarly to sBMP-2, iBMP-2 triggered Smad 1/5 phosphorylation and translocation of the complex to the nucleus, corresponding to the activation of BMP-mediated Smad-dependent pathway. Additionally, successful suppression of myotube formation was observed after 6 days in sBMP-2 and iBMP-2. We next implemented this approach in the fabrication of cFN micropatterned stripes by soft lithography. These stripes allowed cell-surface interaction only on the patterned cFN, since the surface in between was passivated, thus serving as platform for studies on directed cell migration. During a 10-h observation time, the migratory behavior, especially the cells’ net displacement, was increased in presence of BMP-2. As such, this versatile tool retains the bioactivity of GFs and allows the presentation of ECM adhesive cues.